2018
DOI: 10.1097/rlu.0000000000002246
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic 123I Whole Body Scan Prior to Ablation of Thyroid Remnant in Patients With Papillary Thyroid Cancer

Abstract: Our study suggests a significant role of the pre-therapy I WBS in PTC patients referred for I ablation post-thyroidectomy. The actual I dose that was administered based on the I WBS differed from the dose recommended in the absence of the I WBS in 49% of the cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Better spatial resolution of pretreatment SPECT/CT imaging with a potential impact on institutional treatment planning or clinical decision making was also reported in other reports (23)(24)(25). A consistent finding in most studies is an overall rate of *6% for detection of extracervical metastatic disease.…”
Section: Current Standards: Clinical and Technical Considerations In Rai Imagingsupporting
confidence: 73%
“…Better spatial resolution of pretreatment SPECT/CT imaging with a potential impact on institutional treatment planning or clinical decision making was also reported in other reports (23)(24)(25). A consistent finding in most studies is an overall rate of *6% for detection of extracervical metastatic disease.…”
Section: Current Standards: Clinical and Technical Considerations In Rai Imagingsupporting
confidence: 73%
“…First, the small dose of RAI used in diagnostic scans may not be sufficient to identify all remnant tissue. 24,25 The prevalence of residual tissue would be greater than the reported 90.51%, supporting the use of empiric treatment. Our decision tree also assumes that those patients with negative DxWBS findings are truly disease free.…”
Section: Discussionmentioning
confidence: 86%
“…Other authors also demonstrated that the information gained by [ 123 I] DxWBS changed the applied [ 131 I] activity in 49% of cases [ 35 ]. Santhanam and colleagues, in a recent meta-analysis, described a 94% sensitivity of [ 124 I] PET/CT in postoperative detection of metastatic lesions amenable to RAI [ 36 ].…”
Section: Differentiated Thyroid Cancersmentioning
confidence: 99%